Cultural public relations approach to angklung bamboo musical instrument craft workshop activities - Gustini, Leili Kurnia; Hidayat, Dasrun; Aulia, Ellena Fitri; Karamani, Dinar Dina (PRofesi Humas, 2023)
Background: In preserving cultural sustainability, one needed to be done is to maintain cultural resilience. Saung Angklung Udjo (SAU) producing bamboo craft workshop activities in order to do so. The workshop is part of a Public Relations event that is carried out on an ongoing basis. However, there is a need of strategy to have that workshop run optimally. Purpose: This study aimed to determine the design of a public relations event program in the form of a bamboo craft workshop at SAU. Methods: Six informants were involved and determined purposively, including workshop organizers, presenters, and workshop participants. Results: The results of this study show the existence of workshop stages relevant to the IPPAR model (Insight, Program Strategic, Program Implementation, Action, and Reputation). Insight is the initial preparation stage or situation analysis. Program strategy is the planning stage in the form of a program strategy. Program implementation is the implementation stage, and action and reputation is a public assessment as feedback from activities implementation. Conclusion: Public relations events are needed to manage the image and reputation of Angklung’s cultural values. Implications: The results of this study are expected to impact local government policies in managing cultural arts events. The results of this study can also be used as a development of public relations event studies in the context of culture or cultural public relations.